Household formation in post-apartheid South Africa, 1995-2011: Measurement and Trends - Thornton, Amy Julia (School of Economics, 2022)
Who is in your household, what they have to share with you, and who does what, has profound implications for your welfare and well-being. Child welfare and progress through school; continued female disadvantage in the labour market and gender-based violence; livelihood strategies and physical health - these are just a few social outcomes that are fundamentally structured by the household. Change in most outcomes, therefore, cannot be abstracted from change in households. In South Africa, households have been changing in systematic ways. Between the first census of the post-apartheid period in 1996, and the latest in 2011, the number of households increased by 62% from 9 million to 14.5 million. By contrast, the population only grew by 28%, so that the average household shrank by almost a whole person. A notable aspect of this change is an extensive increase in the rate at which people live alone: the number of households that were single-person increased by 160% over the same time period. In other words, over time the South African population has been spread more thinly over fewer households, with direct implications for a sweeping set of social outcomes of importance to the post-apartheid project. A large literature on the topic of household composition exists for South Africa, and many researchers have noted the decline in average household size. Relatively fewer studies, however, aim to uncover the process by which this is happening, and those that do, mainly rely on highly localised data. Indeed, the question of why South Africans would form more and smaller households is particularly provoking given that economic circumstances have arguably been challenging in the post-apartheid period, characterised by high and persistent levels of unemployment and extreme wage inequality. As such, this thesis set out to investigate the process of household formation in the post-apartheid period, and how this aligned with known drivers of household formation in the economic literature, being aging, employment, and marriage. To do this, we construct a harmonised series of nationally-representative cross-sectional household surveys collected (almost) annually by Statistics South Africa, covering the period 1995-2011. Our first contribution is to make progress towards overcoming serious data quality issues in these surveys that undermine not only our study, but most studies seeking to relate people to households in data. We then turn towards analysing household formation, which raises the question of how to measure this process. We approach household formation from two angles: firstly, the aggregate household count by studying household heads, and secondly, the process of leaving the parental household by studying young adults. By tracing trends in household headship, we are able to describe which groups have become more or less likely to form households, and how this changed over the period between 1995 and 2011. Thanks to our attention to data quality, we are able to use the surveys to do the same for single-person households, a sub-group of special interest, in a way that is reliable for the first time. Our third contribution is to describe macro level trends in leaving the parental household, also for the first time for South Africa. Our key finding is that household formation in post-apartheid South Africa has been profoundly impacted by the steady decline of marriage over the same period. As such, household formation patterns are highly gendered, and modulated by men and women's differential access to labour market and grant income, over the life-cycle.